Proposal to strengthen parent-child bonds in the future generations regarding the new ITs and comunication - Gálvez Manrique, Daniela (2019)
At present the use of new trends on technology and communication are becoming more and more relevant in general but especially in families. Among families, if technology and communication are not used wisely they may bring up difficulties. The purpose of this research is to design a proposal to strengthen the parents’ bonds of future generations in connection to information and communication technologies. We would like to explain the anthropological foundations of the person and the family, the essential elements that strengthen parents-child bonds, define concepts from the existing literature review on the influence of new information and communication technologies on children whose parents are millennials. This research follows the bibliographic method and within the methodological approach it is a qualitative research, descriptive and interpretative, with a humanistic line. As for data collection, we consider documentary observation which was used as instruments, in addition to bibliographic, textual, synthesis and summary notes, which allowed the adequate organization of the information obtained from the different printed and digital sources: books, magazines and others. About the ethical criteria we have considered the respect for the person, the search for common interest, justice, and respect for the family; as for the criteria of scientific area we included: explanation of the study of the subject under the anthropology of the person and the family, scientific-humanistic approach, always considering the respect for the person and the standardized on the selection of information and sources. Finally, the result of the research was a proposal that covers three key points: the importance of continuous education in schools for parents where they reinforce their knowledge on these issues and become aware of what they are doing wrong or could be improved, the importance of communication between parents and children, the need for periodic digital disconnection and moments to share with the family, and the education of affectivity, which will be reflected in the healthy emotional development of children.